LGG-52. BINIMETINIB IN CHILDREN WITH PROGRESSIVE OR RECURRENT LOW-GRADE GLIOMA NOT ASSOCIATED WITH NEUROFIBROMATOSIS TYPE 1: INITIAL RESULTS FROM A MULTI-INSTITUTIONAL PHASE II STUDY. (4th December 2020) - Robison, Nathan; Pauly, Jasmine; Malvar, Jemily; Gardner, Sharon; Allen, Jeffrey; MacDonald, Tobey; Aguilera, Dolly; Baxter, Patricia; Bendel, Anne; Kilburn, Lindsay; Leary, Sarah; Bowers, Daniel; et al.
Abstract: BACKGROUND: RAS/RAF/MEK/ERK pathway activation is the primary driver for most pediatric low-grade gliomas (LGG). Binimetinib is an orally bioavailable MEK1/2 inhibitor found to have significant central nervous system penetration in a preclinical model. OBJECTIVE: The primary objective of this multi-institutional open-label phase II study was to assess preliminary efficacy of binimetinib in progressive pediatric LGG. The study included strata for both neurofibromatosis type I (NF1) and non-NF1 associated tumors, as well as a target validation (surgical) stratum. NF1 and surgical strata remain open to enrollment and will be reported separately. METHODS: Children aged 1–18 years with previously treated recurrent or progressive LGG were eligible. The dose of binimetinib was 32 mg/m 2 /dose twice daily. Partial and minor responses were defined, respectively, as 50% and 25% decrease in maximal two-dimensional measurements. RESULTS: Fifty-seven eligible patients without NF1, median age 8 years, were enrolled and began treatment; 26 were female; 28 had documented KIAA1549-BRAF fusion. Eleven patients discontinued drug in the first year due to toxicity, and an additional 27 required dose reduction. The most common drug-attributable grade 3 toxicities included creatine kinase elevation (n=9 patients), rash (n=8), and truncal weakness (n=8). Truncal weakness improved or resolved with dose reduction or cessation. Grade 4 toxicities included creatine kinase elevation (n=2) and transient colitis (n=1). Of 44 patients with preliminary response data available, 22 (50%) showed a minor (n=7) or partial (n=15) response. CONCLUSION: Binimetinib is active, with manageable toxicities, in children without NF1 with progressive LGG.